Cold War [videorecording (DVD)] - Pawlikowski, Pawel; Pawlikowski, Pawel; Kulig, Joanna, 1982-; Kot, Tomasz, 1977-; Szyc, Borys (Criterion collection, 2019)
Set in the 1950s, an older pianist with plans to defect falls in love with a talented young singer while he is on a state-sponsored trip to gather folk songs in the Polish countryside.